Pembelajaran Berkarakteristik Inovatif Abad 21 pada Materi Kemandirian Karir Peserta didik dengan Metode Pembelajaran Berbasis Masalah (Pbl) di SMK Negeri 1 Adiwerna Tegal - Kurniawati, Erni (Cakrawala: Jurnal Pendidikan, 2022)
Career independence is important for learners to determine the future for their lives. Self-reliance efforts are carried out both in the family, school, and community. If students have mature independence will be ready to plunge into society and ready to compete both in the world of work, the business world and when students continue. The goal in this learning is the effectiveness of the use of problem-based learning methods in increasing the career independence of students of class X DPIB 1 SMK Negeri 1 Adiwerna. in shaping the independence of learners' careers, using direct learning methods and contextual learning. Both methods are well implemented, but for more depth with goal-oriented then, problem-based learning methods are more effectively implemented, because learners can openly understand about careers more broadly. Can analyze about the type of career type, and learners can understand about the potential they have and can take decisions about the career so that learners can be more independent in determining their lives.